2016
DOI: 10.1152/ajpheart.00047.2016
|View full text |Cite
|
Sign up to set email alerts
|

The role of perfusion in the oxygen extraction capability of skin and skeletal muscle

Abstract: Oxygen extraction (OE) by all cells is dependent on an adequate supply of oxygen in proximal blood vessels and the cell's need and ability to uptake that oxygen. Here the role of blood flow in regulating OE in skin and skeletal muscle was investigated in lean and obese men. OE was derived by two optical reflectance spectroscopy techniques: 1) from the rate of fall in mean blood saturation during a 4 min below knee arterial occlusion, and thus no blood flow, in calf skin and skeletal muscle and 2) in perfused, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
17
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 9 publications
(18 citation statements)
references
References 43 publications
1
17
0
Order By: Relevance
“…Oxygen removal (consumption) by the tissue was estimated as the rate of oxygen desaturation from the decrease in the oxyHb signal during the first 60 s of arterial occlusion (Boas et al, 2011;Thorn et al, 2016). Oxygen removal (consumption) by the tissue was estimated as the rate of oxygen desaturation from the decrease in the oxyHb signal during the first 60 s of arterial occlusion (Boas et al, 2011;Thorn et al, 2016).…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…Oxygen removal (consumption) by the tissue was estimated as the rate of oxygen desaturation from the decrease in the oxyHb signal during the first 60 s of arterial occlusion (Boas et al, 2011;Thorn et al, 2016). Oxygen removal (consumption) by the tissue was estimated as the rate of oxygen desaturation from the decrease in the oxyHb signal during the first 60 s of arterial occlusion (Boas et al, 2011;Thorn et al, 2016).…”
Section: Discussionmentioning
confidence: 99%
“…Mean resting values for the oxygenation signals recorded at the forearm (oxyHb, deoxyHb, total Hb and S tO 2 ) were calculated throughout the 5 min before arterial occlusion. Oxygen removal (consumption) by the tissue was estimated as the rate of oxygen desaturation from the decrease in the oxyHb signal during the first 60 s of arterial occlusion (Boas et al, 2011;Thorn et al, 2016).…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Recent studies in vivo using time series analysis of simultaneously recorded skin blood flux (BF) and oxygenation (OXY) have shown that these signals oscillate over broad, generally similar frequency ranges, with varying total power and relative contribution from low and high frequency power spectral density (PSD) bands [20,21]. They have further shown that the oscillatory properties of blood flux and oxygenation may influence oxygen extraction [22,23]. It remains unclear, however, whether alterations in perfusion complexity and flowmotion control may have functional significance for oxygen delivery and exchange within the microvasculature.…”
mentioning
confidence: 99%